Study of alterations in pharmacokinetics and pharmacodynamics of Saxagliptin in the presence of Rutin: An interaction study in rats - Naga Raju Kandukoori, Pavani Uppu, Narsimha Reddy Yellu (Journal of Applied Pharmaceutical Science, 2020)
The metabolism of most of the antidiabetic drugs is influenced by cytochrome P-450 (CYP) enzymes in the human body. The activity of these CYP enzymes is affected by the phytoconstituents which are present in vegetables, fruits and some ayurvedic preparations. In the present study, the effect of Rutin on the metabolism of Saxagliptin was studied. The drug was administered alone as well as in combination with Rutin to male albino Wistar rats for 8 days. The blood samples were collected periodically and all the pharmacokinetic parameters, like maximum concentration of drug in serum (Cmax), time required to get Cmax (tmax), area under curve (AUC), mean residence time, volume of distribution (Vd), and total drug clearance (ClT), were determined and compared. The glucose levels were also estimated and compared. From the results, it could be concluded that Rutin has induced the activity of CYP 3A4 enzyme, thereby increasing the metabolism of the drug which ultimately lead to the decrease in Cmax and AUC. Rutin could lower the antidiabetic effect of the drug.
Keywords: Rutin, Saxagliptin, pharmacokinetics, pharmacodynamics, CYP 3A4.